Towards Equitable Higher Education Access: Implications of the Government Students Loans Scheme in Supporting Needy Students in Tanzania - Sululu, Jacob; George, Victor; Kahimba, Joseph (International Journal of African Higher Education, 2025)
This paper examines the students’ loans scheme of the Government of Tanzania and its effects on equitable higher education access for students from poor households. Specifically, the paper looks at the method used by the Tanzania Higher Education Students’ Loans Board (HESLB) to identify the needy students and the loan allocation criteria. The data for this article was obtained from survey of 480 continuing HESLB beneficiaries and key informants, including four Deans of Students, two HESLB officers, and four Loans Desk officers from sampled Higher Learning Institutions. The findings revealed that the presence of the higher education students' loan scheme successfully helped many students enroll in higher education and graduate. However, the efficiency of implementing the loan scheme based on the identification of needy students has been questioned, and the amount of loans allocated to students was inadequate compared to the increasing demand. The study recommends the review of the needy students’ identification and allocation criteria, increasing government budget and accountability.